An independent experiment does not support stress-mediated kin discrimination through red squirrel vocalizations. (June 2021) - Hare, Alexander J.; Newman, Amy E.M.; Dantzer, Ben; Lane, Jeffrey E.; Boutin, Stan; Coltman, David W.; McAdam, Andrew G.
Abstract : A wide range of species have been found to differentiate kin from nonkin. However, the ability to recognize kin, or the costs and benefits of discriminating kin from nonkin may depend on particular extrinsic environmental or intrinsic physiological conditions, resulting in context-dependent kin discrimination. North American red squirrels, Tamiasciurus hudsonicus, have previously been shown to be capable of discriminating the territorial calls of kin and nonkin. More recently, post hoc analysis of existing data suggested that kin discrimination might depend on the state of the caller (i.e. acute stress). Here we tested this hypothesis with independently collected data from a repeated-measures playback experiment and found no evidence in support of acute stress mediating kin discrimination. While squirrels were shown to register and respond to playbacks, exposure to a trapping/handling stressor in the caller had no effect on the receiver's response to the calls of kin and nonkin. Furthermore, we found no overall discrimination between the calls of kin and nonkin. These independently collected data instead suggest that the previous post hoc finding consistent with context-dependent kin discrimination was likely a spurious relationship associated with the data from which the post hoc hypothesis was generated rather than representing a real biological relationship. Our findings from this study emphasize the importance of testing post hoc hypotheses with independent experiments. Highlights: We test whether acute stress enhances red squirrel kin discrimination of rattle calls. We found no evidence of stress-mediated or general kin discrimination. These findings falsify a previously posited hypothesis in the literature. Kin discrimination in red squirrels may be more closely linked to food resources.